Application of composite based on magnetite oxide to remove the ofloxacin from aqueous solution - Quy, Bui Minh; Tuan Tu, Tran; Le, Vu Thi Thu; Tung, Vu Quang; Giang, Nguyen Thi Quynh; Quang, Hoang Van (Vietnam Journal of Science and Technology, 2025)
In this research, Chitosan-Fe3O4 composite materials (CS-MNPs) were successfully synthesized using chemical processes. XRD, SEM, TEM, and VSM techniques were employed to analyze the characteristics of the material. To remove the antibiotic ofloxacin (OFX) from aqueous solutions, CS-MNPs were used as an adsorbent. The effects of pH, contact time, initial concentration, and the presence of another antibiotic (ciprofloxacin) in the solution were investigated to evaluate the ability of OFX to adsorb. The experimental data were analyzed using adsorption models, including kinetic models (pseudo-first-order, pseudo-second-order, and Elovich models), isotherm adsorption models (Langmuir, Freundlich, and Temkin models), and the Langmuir competitive adsorption model. After five adsorption-desorption cycles, the material showed high reusability, with an OFX removal efficiency of 50.16%.